Exploring the relationship between system development life cycle and knowledge accumulation in Taiwan's IT industry. Issue 2 (25th July 2012) - Lai, Wen‐Hsiang; Tsen, Hsin‐Cheng
Abstract: Many projects fail because the knowledge learned from them is obtained too late or insufficient (Koenig & Srikantaiah, 2004); 'knowledge in projects', 'knowledge about projects', and 'knowledge from projects' are three types of knowledge that result from project‐based work (Love et al., 2005). This study explores the relationships between the system development life cycle (SDLC) of project management, firm‐level explicit knowledge of organizational knowledge accumulation (OKA), and implicit knowledge of employee knowledge accumulation (EKA) with respect to knowledge accumulation (KA) and knowledge integration (KI). First, it analyzes the competence of SDLC in Taiwan's IT enterprises by adapting expert interviews, analytic hierarchy process (AHP), and fuzzy rule‐based theory. This reveals that system planning (SP) and system analysis (SA) are the most important SDLC phases. Second, based on the above result, this study investigates how the effectiveness of SDLC (ESDLC) correlates with KI, OKA, and EKA. Results indicate that EKA and OKA have obvious mutual influences, and that both show significant impact on ESDLC. Furthermore, KI has positive influence on EKA, but negative influence on OKA.